Quaternized bis-imidazolyl carbon nanotube modified polyurethane coating and preparation method thereof

Modified carboxylated carbon nanotubes with quaternized biimidazolyl groups and mechanically blended with end amino polyurethane to prepare modified polyurethane coatings, which solves the problems of poor antistatic ability and low mechanical properties of polyurethane coatings, and realizes the Improved antistatic and mechanical properties.

CN119432211AInactive Publication Date: 2025-02-14HUBEI BEIXIANG NANMAO TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411789753.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyurethane coatings have shortcomings in antistatic and mechanical properties, with poor antistatic capabilities and low mechanical properties.

Method used

Modified polyurethane coatings were prepared by modifying carboxylated carbon nanotubes with quaternized biimidazolyl groups to form quaternized biimidazolyl carbon nanotubes and mechanically blended with end amino polyurethane.

Benefits of technology

It significantly improves the antistatic and mechanical properties of the coating, enhances the conductivity and intermolecular forces, reduces resistance and stress concentration, and improves the stability and mechanical strength of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432211A_ABST
    Figure CN119432211A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane coatings, and discloses a quaternized bis-imidazolyl carbon nanotube modified polyurethane coating, compared with a pure-phase polyurethane coating, the quaternized bis-imidazolyl carbon nanotube modified polyurethane coating has better antistatic performance and mechanical performance, and by adding carbon nanotubes into the coating, the antistatic performance of the coating is improved, and the antistatic performance of the coating is improved. By utilizing the good conductivity of the carbon nanotubes and constructing an organic-inorganic network structure in the coating, not only is the antistatic ability of the coating improved, but also the mechanical property of the coating is improved, in addition, the conductivity of the surface of the coating can be improved by using the cationic imidazole quaternary ammonium salt, and the quaternary ammonium salt is grafted on the surface of the carbon nanotubes, so that the conductivity of the coating is improved. The anti-static agent has a synergistic effect, further improves the conductivity of the two, reduces the resistance of the coating, improves the anti-static effect of the coating, and improves the stability of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane coatings, in particular to a quaternized bisimidazolyl carbon nanotube modified polyurethane coating and a preparation method thereof. Background Art

[0002] A large amount of static charge accumulated in insulating materials can cause equipment failures, such as deformation of precision instruments, damage to electronic components, etc. Recently, serious fire hazards and explosion accidents caused by static charge accumulation in petrochemical enterprises have made us more vigilant against static electricity disasters. Due to high conductivity and rapid static electricity elimination capabilities, antistatic coatings have been widely used in industrial fields such as aerospace, petroleum storage, electronic / electrical products and chemical engineering. Polyurethane coating is a common coating, but polyurethane itself is an insulating material and is not conductive.

[0003] Antistatic modification of polyurethane coatings has become an important research direction. For this purpose, researchers have done a lot of research, such as the patent of Chinese Patent Publication No. CN102585678A, which discloses an antistatic amino-terminated polyurethane coating and a preparation method, and the patent of Chinese Patent Publication No. CN102186927A, which discloses an antistatic or conductive polyurethane and a preparation method thereof. Although both increase the antistatic ability of the coating, they still have the problems of high addition amount and unsatisfactory antistatic effect. Carbon nanotubes have excellent mechanical, conductive and structural properties, and can form a conductive network in a polymer matrix at a much lower concentration than spherical particles. Due to its high aspect ratio and large specific surface area and other characteristics, carbon nanotubes are used to increase the conductivity of the coating. Quaternary ammonium salt is a cationic surfactant and a conventional antistatic agent. However, at low relative humidity, there are not enough oxygen atoms in water molecules to coordinate with lone pairs in nitrogen atoms to dissociate the quaternary ammonium salt and obtain more free quaternary ammonium cations, and its antistatic ability is low. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a quaternized bisimidazolyl carbon nanotube modified polyurethane coating and a preparation method thereof, which solves the problems of poor antistatic ability and low mechanical properties of the polyurethane coating.

[0005] To achieve the above object, the present invention provides the following technical solution: a quaternized bisimidazolyl carbon nanotube-modified polyurethane coating, wherein the preparation method of the quaternized bisimidazolyl carbon nanotube-modified polyurethane coating comprises the following steps: (1) Ultrasonic dispersion of carboxylated carbon nanotubes in N,N-dimethylformamide, and then adding a condensation agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and a promoter N-ethyldiisopropylamine (DIPEA) thereto, stirring evenly, adding 2-aminoimidazole to react, and after the reaction is completed, filtering, washing with ethanol and deionized water to obtain imidazole-based carbon nanotubes; (2) ultrasonically dispersing imidazole-based carbon nanotubes in acetonitrile solvent, and then adding 2-methylimidazole, acid-binding agent potassium hydroxide, catalyst tetrabutylammonium bromide (TBAB) and 1,4-dibromobutane in sequence while stirring, stirring evenly, heating to the reaction temperature to react, and after the reaction is completed, filtering and washing with ethanol to obtain biimidazole-based carbon nanotubes; (3) ultrasonically dispersing the bisimidazolyl carbon nanotubes in an isopropanol solvent, then adding chlorobutylamine, stirring evenly, refluxing and reacting, and after the reaction is completed, filtering and washing with ethanol to obtain quaternized bisimidazolyl carbon nanotubes; (4) The amino-terminated polyurethane, the defoaming agent polysiloxane, the film-forming aid dipropylene glycol butyl ether and the deionized water are mixed and stirred evenly, and then the dispersant sodium hexametaphosphate, the thickener methyl methacrylate and the quaternized diimidazole carbon nanotubes are added and stirred evenly to obtain the quaternized diimidazole carbon nanotube modified polyurethane coating.

[0006] Preferably, in step (1), the mass ratio of carboxylated carbon nanotubes, N,N-dimethylformamide, 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate, N-ethyldiisopropylamine and 2-aminoimidazole is 10:1800-3000:120-200:80-150:14-32.

[0007] Preferably, in step (1), the reaction temperature is 20-40° C. and the reaction time is 2-6 h.

[0008] Preferably, in step (2), the mass ratio of imidazole carbon nanotubes, acetonitrile, 2-methylimidazole, potassium hydroxide, tetrabutylammonium bromide and 1,4-dibromobutane is 100:2500-4000:120-300:80-200:12-30:180-400.

[0009] Preferably, in step (2), the reaction temperature is 30-60° C. and the reaction time is 24-36 h.

[0010] Preferably, in step (3), the mass ratio of the bisimidazolyl carbon nanotubes, isopropanol and chlorobutylamine is 100:2500-5000:120-300.

[0011] Preferably, in step (3), the reaction temperature is 80-100° C. and the reaction time is 3-8 h.

[0012] Preferably, in step (4), the mass ratio of the amino-terminated polyurethane, polysiloxane, dipropylene glycol butyl ether, deionized water, sodium hexametaphosphate, methacrylate and quaternized bisimidazolyl carbon nanotubes is 100:0.6-1.5:8-20:60-120:1.2-3:0.7-1.5:1.5-5.

[0013] Compared with the prior art, the present invention has the following experimental principles and beneficial technical effects: The invention discloses a quaternized bisimidazolyl carbon nanotube modified polyurethane coating. Firstly, 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate is used as a condensation agent and N-ethyldiisopropylamine is used as a promoter to make the carboxyl group of the carboxylated carbon nanotube and the amino group of 2-aminoimidazole undergo amidation reaction to obtain the imidazolyl carbon nanotube. Then, potassium hydroxide is used as an acid binding agent, tetrabutylammonium bromide is used as a phase transfer catalyst and 1,4-dibromobutane is used as a bridging agent to make the imine group between the imidazolyl carbon nanotube and 2-methylimidazole undergo substitution reaction to form a tertiary amine to obtain the bisimidazolyl carbon nanotube. Then, chlorobutylamine is used as a quaternizing agent to carry out a quaternization reaction on the tertiary amine of the bisimidazolyl carbon nanotube to obtain the quaternized bisimidazolyl carbon nanotube. Finally, the quaternized bisimidazolyl carbon nanotube modified polyurethane coating is prepared by mechanically blending with amino-terminated polyurethane.

[0014] The quaternized bisimidazolyl carbon nanotube-modified polyurethane coating has better antistatic and mechanical properties than pure polyurethane coating. Carbon nanotubes are a common inorganic additive material. Carbon nanotubes are added to the coating, and the good conductivity of the carbon nanotubes is utilized to construct an organic-inorganic network structure in the coating to form conductive channels or conductive micro-regions, thereby improving the conductivity of the coating and reducing the resistance, so that electrons can be easily transmitted in the network structure or jump in the conductive micro-region, thereby reducing the accumulation of charges in the coating and achieving an antistatic effect. In addition, the carbon nanotubes have excellent mechanical properties. When subjected to external stress, the external stress is widely distributed inside the coating through the network structure, thereby avoiding damage caused by stress concentration and further improving the mechanical properties of the coating. In addition, cationic imidazole quaternary ammonium salt is also a commonly used antistatic agent. Its hydrophilic end can not only form a conductive layer with the air side to increase the conductivity of the coating surface, but also adsorb the waterproof molecules on the coating surface, and decompose the quaternary ammonium salt into an ionic state to further reduce the resistance of the coating. Grafting the quaternary ammonium salt on the surface of carbon nanotubes can not only make the two have a synergistic effect, further increase the conductivity between the two, reduce the resistance of the coating, and improve its antistatic effect, but also avoid the phenomenon of unstable antistatic ability of the coating caused by small molecule precipitation, and improve the stability of the coating. The large amount of amino groups introduced on the surface of carbon nanotubes can not only increase the dispersibility of carbon nanotubes, but also react with isocyanate to form strong hydrogen bonds, increase the intermolecular force between carbon nanotubes and polyurethane, and improve the mechanical strength of polyurethane coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the reaction formula of imidazole carbon nanotubes and 1,4-dibromobutane; Figure 2 It is the reaction formula of imidazole carbon nanotubes, 2-methylimidazole and 1,4-dibromobutane; Figure 3 It is the reaction formula of bisimidazolyl carbon nanotubes and chlorobutylamine. DETAILED DESCRIPTION

[0016] To achieve the above object, the present invention provides the following specific implementation methods and examples: A quaternary ammonium bisimidazolyl carbon nanotube modified polyurethane coating, the preparation method of which comprises the following steps: (1) ultrasonically dispersing carboxylated carbon nanotubes in N,N-dimethylformamide at a mass ratio of 10:1800-3000:120-200:80-150:14-32, and then adding a condensing agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and a promoter N-ethyldiisopropylamine (DIPEA) thereto, stirring evenly, adding 2-aminoimidazole and reacting at 20-40°C for 2-6 hours. After the reaction is completed, filtering, washing with ethanol and deionized water to obtain imidazole-based carbon nanotubes; (2) ultrasonically dispersing imidazole-based carbon nanotubes in acetonitrile solvent at a mass ratio of 100:2500-4000:120-300:80-200:12-30:180-400, and then adding 2-methylimidazole, acid-binding agent potassium hydroxide, catalyst tetrabutylammonium bromide (TBAB) and 1,4-dibromobutane in sequence while stirring, stirring evenly, heating to 30-60°C to react for 24-36 hours, and after the reaction is completed, filtering and washing with ethanol to obtain bisimidazole-based carbon nanotubes; (3) ultrasonically dispersing bisimidazolyl carbon nanotubes in an isopropanol solvent at a mass ratio of 100:2500-5000:120-300, then adding chlorobutylamine, stirring evenly, refluxing and reacting at 80-100° C. for 3-8 hours, filtering after the reaction, and washing with ethanol to obtain quaternized bisimidazolyl carbon nanotubes; (4) According to the mass ratio of 100:0.6-1.5:8-20:60-120:1.2-3:0.7-1.5:1.5-5, amino-terminated polyurethane, defoaming agent polysiloxane, film-forming aid dipropylene glycol butyl ether and deionized water are mixed and stirred evenly, and then dispersant sodium hexametaphosphate, thickener methyl methacrylate and quaternized diimidazole carbon nanotubes are added and stirred evenly to obtain a quaternized diimidazole carbon nanotube modified polyurethane coating. Example 1

[0017] (1) 0.5 g of carboxylated carbon nanotubes were ultrasonically dispersed in 90 g of N,N-dimethylformamide, and then 6 g of condensation agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and 4 g of promoter N-ethyldiisopropylamine (DIPEA) were added thereto. After stirring evenly, 0.7 g of 2-aminoimidazole was added and reacted at 20 °C for 2 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain imidazole-based carbon nanotubes. (2) Ultrasonic dispersion of 2 g of imidazole-based carbon nanotubes in 5 g of acetonitrile solvent, and then adding 2.4 g of 2-methylimidazole, 1.6 g of acid-binding agent potassium hydroxide, 0.24 g of catalyst tetrabutylammonium bromide (TBAB) and 3.6 g of 1,4-dibromobutane in sequence while stirring, stirring evenly, heating to 30 ° C for 24 h, and after the reaction is completed, filtering and washing with ethanol to obtain biimidazole-based carbon nanotubes; (3) Ultrasonic dispersion of 2 g of bisimidazolyl carbon nanotubes in 50 g of isopropanol solvent, and then adding 2.4 g of chlorobutylamine, stirring evenly, reflux and react at 80 °C for 3 h. After the reaction is completed, filtering and washing with ethanol to obtain quaternized bisimidazolyl carbon nanotubes; (4) 10 g of amino-terminated polyurethane, 0.06 g of defoaming agent polysiloxane, 0.8 g of film-forming aid dipropylene glycol butyl ether and 6 g of deionized water were mixed and stirred evenly, and then 0.12 g of dispersant sodium hexametaphosphate, 0.07 g of thickener methyl methacrylate and 0.15 g of quaternized diimidazole carbon nanotubes were added and stirred evenly to obtain a quaternized diimidazole carbon nanotube modified polyurethane coating. Example 2

[0018] (1) 0.5 g of carboxylated carbon nanotubes were ultrasonically dispersed in 100 g of N,N-dimethylformamide, and then 7 g of condensation agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and 4.5 g of promoter N-ethyldiisopropylamine (DIPEA) were added thereto. After stirring evenly, 0.8 g of 2-aminoimidazole was added and reacted at 25 °C for 3 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain imidazole-based carbon nanotubes. (2) Ultrasonic dispersion of 2 g of imidazole-based carbon nanotubes in 5.5 g of acetonitrile solvent, and then sequentially adding 3 g of 2-methylimidazole, 2 g of acid-binding agent potassium hydroxide, 0.3 g of catalyst tetrabutylammonium bromide (TBAB) and 4 g of 1,4-dibromobutane under stirring, stirring evenly, heating to 35 ° C for 26 h, after the reaction is completed, filtering, and washing with ethanol to obtain biimidazole-based carbon nanotubes; (3) Ultrasonic dispersion of 2 g of bisimidazolyl carbon nanotubes in 55 g of isopropanol solvent, and then adding 3 g of chlorobutylamine, stirring evenly, reflux and react at 85 °C for 4 h. After the reaction is completed, filtering and washing with ethanol to obtain quaternized bisimidazolyl carbon nanotubes; (4) 10 g of amino-terminated polyurethane, 0.08 g of defoaming agent polysiloxane, 1 g of film-forming aid dipropylene glycol butyl ether and 8 g of deionized water were mixed and stirred evenly, and then 0.16 g of dispersant sodium hexametaphosphate, 0.08 g of thickener methyl methacrylate and 0.2 g of quaternized diimidazole carbon nanotubes were added and stirred evenly to obtain a quaternized diimidazole carbon nanotube modified polyurethane coating. Example 3

[0019] (1) 0.5 g of carboxylated carbon nanotubes were ultrasonically dispersed in 120 g of N,N-dimethylformamide, and then 8 g of condensing agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and 5.5 g of accelerator N-ethyldiisopropylamine (DIPEA) were added thereto. After stirring evenly, 1.2 g of 2-aminoimidazole was added and reacted at 30 °C for 4 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain imidazole-based carbon nanotubes. (2) Ultrasonic dispersion of 2 g of imidazole-based carbon nanotubes in 6.5 g of acetonitrile solvent, and then sequentially adding 4 g of 2-methylimidazole, 2.8 g of acid-binding agent potassium hydroxide, 0.45 g of catalyst tetrabutylammonium bromide (TBAB) and 6 g of 1,4-dibromobutane under stirring, stirring evenly, heating to 45 ° C for 30 h, after the reaction is completed, filtering, and washing with ethanol to obtain biimidazole-based carbon nanotubes; (3) Ultrasonic dispersion of 2 g of bisimidazolyl carbon nanotubes in 75 g of isopropanol solvent, and then adding 4 g of chlorobutylamine, stirring evenly, reflux and react at 90 °C for 6 h. After the reaction is completed, filtering and washing with ethanol to obtain quaternized bisimidazolyl carbon nanotubes; (4) 10 g of amino-terminated polyurethane, 0.1 g of defoaming agent polysiloxane, 1.4 g of film-forming aid dipropylene glycol butyl ether and 9 g of deionized water were mixed and stirred evenly, and then 0.2 g of dispersant sodium hexametaphosphate, 0.1 g of thickener methyl methacrylate and 0.35 g of quaternized diimidazole carbon nanotubes were added and stirred evenly to obtain a quaternized diimidazole carbon nanotube modified polyurethane coating. Example 4

[0020] (1) 0.5 g of carboxylated carbon nanotubes were ultrasonically dispersed in 140 g of N,N-dimethylformamide, and then 9 g of condensation agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and 6.5 g of promoter N-ethyldiisopropylamine (DIPEA) were added thereto. After stirring evenly, 1.4 g of 2-aminoimidazole was added and reacted at 35 °C for 5 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain imidazole-based carbon nanotubes. (2) Ultrasonic dispersion of 2 g of imidazole-based carbon nanotubes in 7 g of acetonitrile solvent, and then sequentially adding 5 g of 2-methylimidazole, 3.5 g of acid-binding agent potassium hydroxide, 0.5 g of catalyst tetrabutylammonium bromide (TBAB) and 7 g of 1,4-dibromobutane under stirring, stirring evenly, heating to 55 ° C for 32 h, after the reaction is completed, filtering, washing with ethanol, and obtaining biimidazole-based carbon nanotubes; (3) Ultrasonic dispersion of 2 g of bisimidazolyl carbon nanotubes in 90 g of isopropanol solvent, and then adding 5 g of chlorobutylamine, stirring evenly, reflux and react at 95 °C for 7 h. After the reaction is completed, filtering and washing with ethanol to obtain quaternized bisimidazolyl carbon nanotubes; (4) 10 g of amino-terminated polyurethane, 0.14 g of defoaming agent polysiloxane, 1.8 g of film-forming aid dipropylene glycol butyl ether and 11 g of deionized water were mixed and stirred evenly, and then 0.36 g of dispersant sodium hexametaphosphate, 0.14 g of thickener methyl methacrylate and 0.45 g of quaternized diimidazole carbon nanotubes were added and stirred evenly to obtain a quaternized diimidazole carbon nanotube modified polyurethane coating. Example 5

[0021] (1) 0.5 g of carboxylated carbon nanotubes were ultrasonically dispersed in 150 g of N,N-dimethylformamide, and then 10 g of condensation agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and 7.5 g of promoter N-ethyldiisopropylamine (DIPEA) were added thereto. After stirring evenly, 1.6 g of 2-aminoimidazole was added and reacted at 40 °C for 6 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain imidazole-based carbon nanotubes. (2) Ultrasonic dispersion of 2 g of imidazole-based carbon nanotubes in 8 g of acetonitrile solvent, and then adding 6 g of 2-methylimidazole, 4 g of acid-binding agent potassium hydroxide, 0.6 g of catalyst tetrabutylammonium bromide (TBAB) and 8 g of 1,4-dibromobutane in sequence while stirring, stirring evenly, heating to 60 ° C for 36 h, and after the reaction is completed, filtering and washing with ethanol to obtain biimidazole-based carbon nanotubes; (3) Ultrasonic dispersion of 2 g of bisimidazolyl carbon nanotubes in 100 g of isopropanol solvent, and then adding 6 g of chlorobutylamine, stirring evenly, reflux and react at 100 °C for 8 h. After the reaction is completed, filtering and washing with ethanol to obtain quaternized bisimidazolyl carbon nanotubes; (4) 10 g of amino-terminated polyurethane, 0.15 g of defoaming agent polysiloxane, 2 g of film-forming aid dipropylene glycol butyl ether and 12 g of deionized water were mixed and stirred evenly, and then 0.3 g of dispersant sodium hexametaphosphate, 0.15 g of thickener methyl methacrylate and 0.5 g of quaternized diimidazole carbon nanotubes were added and stirred evenly to obtain a quaternized diimidazole carbon nanotube modified polyurethane coating.

[0022] Comparative Example 1 (1) 0.5 g of carboxylated carbon nanotubes were ultrasonically dispersed in 90 g of N,N-dimethylformamide, and then 8 g of condensing agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and 5.5 g of accelerator N-ethyldiisopropylamine (DIPEA) were added thereto. After stirring evenly, 0.9 g of 2-aminoimidazole was added and reacted at 25 °C for 3 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain imidazole-based carbon nanotubes. (2) Ultrasonic dispersion of 2 g of imidazole-based carbon nanotubes in 6 g of acetonitrile solvent, and then sequentially adding 5 g of 2-methylimidazole, 3 g of acid-binding agent potassium hydroxide, 0.5 g of catalyst tetrabutylammonium bromide (TBAB) and 6 g of 1,4-dibromobutane under stirring, stirring evenly, heating to 35 ° C for 28 h, and after the reaction is completed, filtering and washing with ethanol to obtain biimidazole-based carbon nanotubes; (3) 10 g of amino-terminated polyurethane, 0.1 g of defoaming agent polysiloxane, 1 g of film-forming aid dipropylene glycol butyl ether and 9 g of deionized water were mixed and stirred evenly, and then 0.2 g of dispersant sodium hexametaphosphate, 0.08 g of thickener methyl methacrylate and 0.35 g of diimidazole carbon nanotubes were added and stirred evenly to obtain a quaternary ammonium diimidazole carbon nanotube modified polyurethane coating.

[0023] The resistivity of quaternary ammonium bisimidazolyl carbon nanotube modified polyurethane coating was tested according to the national standard GB / T 11210-2014.

[0024]

[0025] The mechanical strength test of quaternary ammonium bisimidazolyl carbon nanotube modified polyurethane coating was carried out according to the national standard GB / T 1732-1979 (88).

[0026]

Claims

1. A quaternary ammonium bisimidazolyl carbon nanotube modified polyurethane coating, characterized in that: The preparation method of the quaternized bisimidazolyl carbon nanotube modified polyurethane coating comprises the following steps: (1) Ultrasonic dispersion of carboxylated carbon nanotubes in N,N-dimethylformamide, and then adding a condensation agent 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU) and a promoter N-ethyldiisopropylamine (DIPEA) thereto, stirring evenly, adding 2-aminoimidazole to react, and after the reaction is completed, filtering, washing with ethanol and deionized water to obtain imidazole-based carbon nanotubes; (2) ultrasonically dispersing imidazole-based carbon nanotubes in acetonitrile solvent, and then adding 2-methylimidazole, acid-binding agent potassium hydroxide, catalyst tetrabutylammonium bromide (TBAB) and 1,4-dibromobutane in sequence while stirring, stirring evenly, heating to the reaction temperature to react, and after the reaction is completed, filtering and washing with ethanol to obtain biimidazole-based carbon nanotubes; (3) ultrasonically dispersing the bisimidazolyl carbon nanotubes in an isopropanol solvent, then adding chlorobutylamine, stirring evenly, refluxing and reacting, and after the reaction is completed, filtering and washing with ethanol to obtain quaternized bisimidazolyl carbon nanotubes; (4) The amino-terminated polyurethane, the defoaming agent polysiloxane, the film-forming aid dipropylene glycol butyl ether and the deionized water are mixed and stirred evenly, and then the dispersant sodium hexametaphosphate, the thickener methyl methacrylate and the quaternized diimidazole carbon nanotubes are added and stirred evenly to obtain the quaternized diimidazole carbon nanotube modified polyurethane coating.

2. The quaternized bisimidazolyl carbon nanotube modified polyurethane coating according to claim 1, characterized in that: In the step (1), the mass ratio of carboxylated carbon nanotubes, N,N-dimethylformamide, 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate, N-ethyldiisopropylamine and 2-aminoimidazole is 10:1800-3000:120-200:80-150:14-32.

3. The quaternized bisimidazolyl carbon nanotube modified polyurethane coating according to claim 1, characterized in that: In the step (1), the reaction temperature is 20-40° C. and the reaction time is 2-6 h.

4. The quaternized bisimidazolyl carbon nanotube modified polyurethane coating according to claim 1, characterized in that: In the step (2), the mass ratio of imidazole carbon nanotubes, acetonitrile, 2-methylimidazole, potassium hydroxide, tetrabutylammonium bromide and 1,4-dibromobutane is 100:2500-4000:120-300:80-200:12-30:180-400.

5. The quaternized bisimidazolyl carbon nanotube modified polyurethane coating according to claim 1, characterized in that: In the step (2), the reaction temperature is 30-60° C. and the reaction time is 24-36 hours.

6. The quaternized bisimidazolyl carbon nanotube modified polyurethane coating according to claim 1, characterized in that: In the step (3), the mass ratio of the bisimidazolyl carbon nanotubes, isopropanol and chlorobutylamine is 100:2500-5000:120-300.

7. The quaternized bisimidazolyl carbon nanotube modified polyurethane coating according to claim 1, characterized in that: In the step (3), the reaction temperature is 80-100° C. and the reaction time is 3-8 h.

8. The quaternized bisimidazolyl carbon nanotube modified polyurethane coating according to claim 1, characterized in that: In the step (4), the mass ratio of the amino-terminated polyurethane, polysiloxane, dipropylene glycol butyl ether, deionized water, sodium hexametaphosphate, methacrylate and quaternized bisimidazolyl carbon nanotubes is 100:0.6-1.5:8-20:60-120:1.2-3:0.7-1.5:1.5-5.

Citation Information

Patent Citations

  • Antistatic or electrically conductive polyurethanes, and method for the production thereof

    CN102186927A

  • Antistatic waterborne polyurethane coating and preparation method thereof

    CN102585678A

Cited By

  • Anti-aging rubber material and preparation method thereof

    CN121673740A